2016
DOI: 10.1089/hum.2016.065
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Perforin Expression Is Required for Effective Correction of Hemophagocytic Lymphohistiocytosis

Abstract: K.R., M.J., and P.M. share senior authorship.Perforin-1 mutations result in a potentially fatal hemophagocytic lymphohistiocytosis (HLH) with heightened immune activation, hypercytokinemia, pancytopenia, and end-organ damage. At present, hematopoietic stem cell (HSC) transplantation is curative, but limited by donor availability and associated mortality, making gene therapy an attractive alternative approach for HLH. We reported that perforin expression driven by cellular promoters in lentiviral (LV) vectors r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…103 X-linked lymphoproliferative disease (XLP), a T and NK lymphoproliferative disorder caused by mutations in the signaling adaptor signaling lymphocytic activation molecule (SLAM)-associated protein (SAP), and familial hemophagocytic lymphohistiocytosis (FHLH), a hemophagocytic disease resulting from defective NK and CD8 + T cell cytotoxicity, are potential candidates for both HSC/P and peripheral T cell-based approaches. [104][105][106] SAP is involved in multiple signaling pathways that affect proliferation, apoptosis, and differentiation, whereas perforin and Munc13-4, which are the most commonly deficient proteins in FHLH, are direct effectors of cytotoxicity. Lineage-restricted regulation of these genes might be required to avoid deleterious effects in cells where these proteins are not normally expressed.…”
Section: Preclinical Development Of Gene Therapy For Other Candidate mentioning
confidence: 99%
“…103 X-linked lymphoproliferative disease (XLP), a T and NK lymphoproliferative disorder caused by mutations in the signaling adaptor signaling lymphocytic activation molecule (SLAM)-associated protein (SAP), and familial hemophagocytic lymphohistiocytosis (FHLH), a hemophagocytic disease resulting from defective NK and CD8 + T cell cytotoxicity, are potential candidates for both HSC/P and peripheral T cell-based approaches. [104][105][106] SAP is involved in multiple signaling pathways that affect proliferation, apoptosis, and differentiation, whereas perforin and Munc13-4, which are the most commonly deficient proteins in FHLH, are direct effectors of cytotoxicity. Lineage-restricted regulation of these genes might be required to avoid deleterious effects in cells where these proteins are not normally expressed.…”
Section: Preclinical Development Of Gene Therapy For Other Candidate mentioning
confidence: 99%
“…4 In addition to HSCT, gene therapy of hematopoietic stem cells has been tested as a treatment of FHL2 in a murine model. 8,9 Given that the main defect in FHL disease is cytotoxic dysfunction of mature T cells, the latter constitute a potentially valuable target for gene therapy approaches. The genetic modification of T cells has produced remarkable clinical outcomes in cancer immunotherapy and in cases of adenosine deaminase deficiency.…”
mentioning
confidence: 99%
“…In diseases like LAD (11), CGD (13,14), and WAS (15,16), where a high level of transgene expression is required to achieve a therapeutic benefit, cellular promoters were insufficient to mediate a therapeutic effect unless high VCN were present and strong enhancers were used. In fact, we have recently reported that expression of perforin from cellular or endogenous promoters in LV only partially corrects the hemophagocytic lymphohistiocytosis (HLH) phenotype, and strong viral enhancers are necessary for complete disease phenotype correction (55).…”
Section: Discussionmentioning
confidence: 99%